The impact of students’ business success to their academic performance - Lili Adi Wibowo; Indra Cahya Uno; Lisnawati Lisnawati; Tika Annisa Koeswandi (Journal of Business Management Education (JBME), 2023)
This research is a quantitative descriptive research that aims to describe the impact of students' business success (X) to their educational performance (Y). To analyze the data, the Statistical Package for Social Sciences (SPSS) version 24.0 for windows was used. Validity and reliability tests were carried out using Cronbach Alpha. The sample involved was 443 students who were successful in doing business through The Ambassador of Business Edupreneur program at the Faculty of Economics and Business Education, Indonesian University of Education. The results of this study conclude that there is a relationship and influence between students' business success (X) to their academic performance (Y). The higher the students' business success (X), the higher their academic performance (Y).